2007
DOI: 10.1007/s00265-007-0385-3
|View full text |Cite
|
Sign up to set email alerts
|

Production of sexuals in a fission-performing ant: dual effects of queen pheromones and colony size

Abstract: Models based on the kin selection theory predict that in social hymenopterans, queens may favor a lower investment in the production of sexuals than workers. However, in perennial colonies, this conflict may be tuned down by colony-level selection because of the trade off between colony survival and reproductive allocation. In this study, we present a survey of sexual production in colonies of Aphaenogaster senilis, a common species of ant in the Iberian Peninsula. Similar to most species that reproduce by fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 61 publications
3
56
1
Order By: Relevance
“…Proximately, such a shift in the allocation of resources may have resulted from a qualitative change in colonies' resource intake, such as an increase in the proportion of proteins or lipids, which is known to affect the production of sexuals, as well as the sex ratio in other species (Deslippe and Savolainen 1995, Bono and Herbers 2003, Brown and Keller 2006. In A. senilis, queens are produced in very small numbers and only in large or queenless colonies (Boulay et al 2007b). It has been suggested that queens are actually produced only after fission (Ledoux 1971), which explains why we did not find unmated queens in the colonies excavated just before the reproductive season.…”
Section: Discussionmentioning
confidence: 99%
“…Proximately, such a shift in the allocation of resources may have resulted from a qualitative change in colonies' resource intake, such as an increase in the proportion of proteins or lipids, which is known to affect the production of sexuals, as well as the sex ratio in other species (Deslippe and Savolainen 1995, Bono and Herbers 2003, Brown and Keller 2006. In A. senilis, queens are produced in very small numbers and only in large or queenless colonies (Boulay et al 2007b). It has been suggested that queens are actually produced only after fission (Ledoux 1971), which explains why we did not find unmated queens in the colonies excavated just before the reproductive season.…”
Section: Discussionmentioning
confidence: 99%
“…In Doñana National Park (southern Spain), A. senilis is particularly abundant in xeric sandy areas dominated by open scrublands. Colonies are strictly monogynous (1 queen per colony) and contain between 200 and 3000 workers (Boulay et al 2007). This species occupies a relatively low rank in the community behavioral dominance hierarchy: it is a subordinate, risk-prone species that forages very close to its critical thermal maximum-the temperature at which locomotor ability is so reduced that individuals can no longer escape lethal temperatures (Cerdá et al 1998a).…”
Section: Colony Maintenance and Experimental Conditionsmentioning
confidence: 99%
“…An internal standard (eicosane) was added to the extract or deposited on the fiber to measure the hydrocarbon quantities. Hydrocarbons of A. senilis were previously identified [24,25] and we added some new compounds present in very small quantities.…”
Section: Chemical Analysesmentioning
confidence: 99%